Virtual 3D Modeling of Airways in Congenital Heart Defects - Speggiorin, Simone; Durairaj, Saravanan; Mimic, Branko; Corno, Antonio F. (Frontiers in Pediatrics, 2016)
The involvement of the airway is not uncommon in the presence of complex cardiovascular malformations. In these cases, a careful inspection of the relationship between the airway and the vasculature is paramount to plan the surgical procedure. Three-dimentional printing enhanced the visualization of the cardio-vascualr structure. Unfortunately IT does not allow to remove selected anatomy to improve the visualization of the surrounding ones. Computerized modelling (CM) of has the potential to fill this gap by allowing a dynamic handling of different anatomies, increasing the exposure of vessels or bronchi to show their relationship.. We started to use this technique to plan the surgical repair in these complex cases where the airway is affected. This technique is routinely used in our Institution as an additional tool in the pre-surgical assessment. We report 4 cases in which the airways were compressed by vascular structures : ascending aorta in 1, left pulmonary artery sling in 1, Patent ductus arteriosus (PDA) in 1 and major aorto-pulmonary collateral artery in 1. We believe this technique can enhance the understanding of the causes of airway involvement and facilitate the creation of an appropriate surgical plan.